Methodological developments in ethnography - Walford, Geoffrey (Amsterdam ; Oxford : Elsevier JAI, 2007)
What counts as ethnography and what counts as good ethnographic methodology are both highly contested. This volume brings together chapters presenting a diversity of views on some of the current debates and developments in the field. It does not try to present a single coherent view but, through its heterogeneity, illustrates the strength and impact of debate. The topics discussed include participant observation, research roles in fieldwork, access to places and people in research, ethical issues concerning anonymity and intimacy in research, generalization in ethnography, the use of video, developing stronger criteria for autoethnography, and the use of ethnography as a contribution to the generation and modification of indicators. Together the collection illustrates the strength and vitality of ethnography.
Description based on print version record.
Keywords: Educational anthropology -- Methodology; Physical anthropology & ethnography; Social Science -- Demography; Education -- Research